Radiação eletromagnética não ionizante e o declínio das abelhas : uma abordagem interdisciplinar por meio do enfoque ciência, tecnologia, sociedade e ambiente - Silva, Crisilandia de Nave da (2022)
Faced with the constant changes that happen in contemporary society, characterized by an intense flow of information, a teaching of Physics focused on everyday situations, which relates school contents with the reality of students, can make it possible to understand the applications knowledge in society. contemporary culture, in addition to contributing to a critical and reflective citizen education. Thus, teachers are challenged to seek teaching methodologies that contribute to their pedagogical practice and to the physics learning process. Therefore, the present work aims to investigate the contributions of interdisciplinarity, as a methodological strategy in the teaching and learning process for the understanding of concepts and sensitization of the socio-scientific posture of students of the 3rd year of high school, through the Educational Product “The decline of bees associated with the effects of non-ionizing radiation: interdisciplinarity through the Science, Technology, Society and Environment approach”. To carry out this study, we classified the research, in terms of its approach, as qualitative, applied in nature, exploratory and descriptive in terms of objectives; in relation to procedures, it was classified as action research, bibliographic and documentary. The following instruments were used for data collection: previous and subsequent questionnaires applied to the students and the teacher, notes in the researcher teacher's field notebook and recordings of the classes. For the analysis of the data produced, we took into account the guidelines of Discursive Textual Analysis (DTA). The theoretical foundation is based on the Three Pedagogical Moments, on interdisciplinarity and on the principles of the Science, Technology, Society and Environment (CTSA) approach. The study carried out from the bibliographic survey of scientific works, indicated a shortage of teaching materials aimed at approaching the theme "Non-ionizing electromagnetic radiation associated with the decline of bees", as well as showing a low production of works that address related topics. non-ionizing radiation in the interdisciplinary perspective in high school classes. The analysis of the data produced revealed that the research subjects, students and biology teacher, did not have preliminary knowledge about the biological effects of non-ionizing electromagnetic radiation on bee health. During the application of the intervention in a pandemic scenario, we observed that the Educational Product - Pedagogical Support Material, composed of a Student Booklet, a Didactic Sequence for the Teacher and two videos, and the teaching methodology, contributed to fostering interdisciplinary discussions about the theme, promoting student interaction and reflection on the situations discussed. Based on the analysis process, we also evidenced: a) acquisition and improvement of physical concepts; b) understanding of the applications of non-ionizing radiation in technologies and the risks of radiation to the survival of bees; c) association of knowledge about non-ionizing radiation with technological, environmental, social, ethical and economic issues. Therefore, we believe that the interdisciplinary and socio-scientific bias can favor the understanding of situations experienced by students and enrich the teacher's pedagogical practice, overcoming fragmented and decontextualized teaching.